Insights into microbiome-triterpenoid correlation in Poria cocos via comparative analysis of sclerotial and soil microenvironments - Zheng, Mingzhu; Zhong, Can; Pan, Gen; Xie, Jing; Zhang, Shuihan; Jin, Jian (Frontiers in Microbiology, 2025)
IntroductionPoria cocos (P. cocos) is a medicinal fungus renowned for its bioactive triterpenoids, particularly pachymic acid. However, the relationship between its specialized microbiota and the accumulation of this key metabolite remains poorly understood.MethodsThis study systematically compared the microbial communities and pachymic acid distribution patterns between P. cocos and different soil microenvironments using integrated 16S rRNA/ITS1 sequencing and HPLC-QTOF-MS/MS analysis.ResultsThe results revealed significantly lower microbial diversity in P. cocos compared to the surrounding soil, with a dominance of Proteobacteria and Ascomycota, along with specific enrichments of Burkholderia-Caballeronia-Paraburkholderia and Scytalidium. Pachymic acid was found to accumulate predominantly within the sclerotia, with trace amounts detectable in adjacent soils. Significant positive correlations were identified between pachymic acid and these enriched microbial taxa.DiscussionThese findings indicate that P. cocos forms a specialized microenvironment characterized by selective microbial enrichment associated with pachymic acid accumulation, offering valuable insights for optimizing cultivation strategies to improve its medicinal quality.